2014
DOI: 10.1093/infdis/jiu606
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of an Adjuvanted Herpes Zoster Subunit Candidate Vaccine in HIV-Infected Adults: A Phase 1/2a Randomized, Placebo-Controlled Study

Abstract: Background. Human immunodeficiency virus (HIV)–infected individuals are at increased risk of herpes zoster (HZ), even in the antiretroviral therapy (ART) era. Because concerns exist about the use of live-attenuated vaccines in immunocompromised individuals, a subunit vaccine may be an appropriate alternative.Methods. This phase 1/2, randomized, placebo-controlled study evaluated the immunogenicity and safety of an investigational HZ subunit vaccine (HZ/su). Three cohorts of HIV-infected adults aged ≥18 years w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
150
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 25 publications
1
150
0
8
Order By: Relevance
“…2,18,19 An investigational herpes zoster subunit vaccine (HZ/su; GSK Vaccines) containing VZV glycoprotein E and the AS01 B adjuvant system is being evaluated for the prevention of herpes zoster and postherpetic neuralgia in adults 50 years of age or older. [20][21][22][23][24][25] A previous trial (Zoster Efficacy Study in Adults 50 Years of Age or Older showed that HZ/su had a vaccine efficacy against herpes zoster of 97.2%, which was consistent across all age groups. 26 Although 24% of the participants in ZOE-50 were 70 years of age or older, the trial was not intended to definitively assess vaccine efficacy against herpes zoster or postherpetic neuralgia in this age group.…”
mentioning
confidence: 88%
“…2,18,19 An investigational herpes zoster subunit vaccine (HZ/su; GSK Vaccines) containing VZV glycoprotein E and the AS01 B adjuvant system is being evaluated for the prevention of herpes zoster and postherpetic neuralgia in adults 50 years of age or older. [20][21][22][23][24][25] A previous trial (Zoster Efficacy Study in Adults 50 Years of Age or Older showed that HZ/su had a vaccine efficacy against herpes zoster of 97.2%, which was consistent across all age groups. 26 Although 24% of the participants in ZOE-50 were 70 years of age or older, the trial was not intended to definitively assess vaccine efficacy against herpes zoster or postherpetic neuralgia in this age group.…”
mentioning
confidence: 88%
“…gE is abundantly expressed on the surface of varicellazoster virions and by infected cells, and appears to be a major target for VZV-specific CD4 + T-cell responses [24]. HZ/su was also designed to address the burden of herpes zoster in the immunocompromised population [25,26], where live-attenuated vaccine is contraindicated [27].…”
Section: Plasmodium and Varicella-zoster Virus: Two Pathogens With Comentioning
confidence: 99%
“…The safety and efficacy of the HZ/su vaccine within immunocompromised groups has been investigated in two phase I/II single-blind randomized trials among autologous hematopoietic cell transplant recipients with hematologic malignancies [120] and among antiretroviral treated or naïve HIV-infected adults with CD4 T cell counts ranging from 50 to >500 cells/ml [121]. Both trials showed immunogenicity similar to that in healthy patients and no vaccination-related serious adverse effects were reported.…”
Section: Zoster Vaccine – Unresolved Questionsmentioning
confidence: 99%